Local Community Empowerment in The Special Autonomy Law in Papua Province - PAKASI, USMAN (Jurnal Studi Pemerintahan, 2012)
The establishment of the 2001 Special Autonomy Law in Papua Province is not exempted fromeconomic, political and socio-cultural problems. The law is intended to empower the people bypreserving their interests and upholding the basic rights of native Papuans. This research aims atfinding out a theoretical understanding on the forms of local community empowerment during theimplementation of special autonomy in Papua Province. The study is performed through a qualitativeapproach with a phenomenological strategy. The research was conducted at a location in Jayapura.Empirical data were obtained using the techniques of observation, in-depth interviews, and othersecondary data. The implementation of Special Autonomy in Papua Province has brought forth afundamental change in the approaches and policies of community development, particularly localcommunity empowerment that includes indigenous communities, women, and religion. Localcommunity empowerment in the economic and socio-cultural aspects represents the effort to improvethe welfare and sense of justice within the local community in development.